AUDITING THE COUNTRY-LEVEL TAX COMPLIANCE SITUATION: RECENT FINDINGS FOR THE CASE OF ROMANIA - Ionel BOSTAN; Bogdan Narcis FIRTESCU; Laurențiu DROJ (Oradea Journal of Business and Economics)
This paper analyzes the recent state of tax compliance in Romania through a detailed assessment (external public audit) of the specific activities carried out by the National Agency for Fiscal Administration (ANAF). The study is structured into four main sections: an introduction covering key budgetary aspects, an overview of ANAF’s organization, functions, and performance, an analysis of the audit conducted by the Romanian Court of Accounts (for the 2022 fiscal year, audited in 2023), and a set of recommended measures to enhance ANAF’s efficiency in mitigating tax non-compliance risks. The external public audit identified significant irregularities in tax revenue collection and administration, revealing systemic deficiencies that hinder effective fiscal governance. The audit’s key findings include procedural gaps, legislative shortcomings, and ineffective digitalization strategies. Based on these findings, the study proposes legislative and operational improvements, investments in digital infrastructure, and the optimization of risk management. These recommendations aim to strengthen ANAF’s capacity to ensure tax compliance, reduce the budget deficit, and develop a transparent and efficient tax system. The conclusions emphasize the importance of proactive reforms in fiscal policy and enhanced institutional oversight for the sustainable management of public finances.